Moisture and humidity sensor - Mahmood, Muhammad Syarafi; Abdul Rahim, Ruzairi; Abas, Khairul Hamimah; Ahmad, Anita (Penerbit UTHM, 2016)
Humidity sensing is important in control system for industrial processes and human comfort (Preeti Jain, 2012). Humidity is the presence of water in air and also presence of water vapor that influences various physical, chemical and biological processes. In industry, humidity measurement is critical due to it may affect the business cost of the product and the health and safety of the worker. One of the applications of the humidity sensor is soil moisture sensor. This sensor is measure the volumetric water content in soil (Arnold, 2015). This sensor measure indirectly by using property of the soil such as electrical resistance, dielectric constant etc. The sensor should calibrate relative to vary environment factor such as soil type, temperature and electric conductivity. Besides, reflected microwave radiation also affected the soil sensor and can be used for remote sensing in hydrology and agriculture. Humidity control is necessary in chemical gas purification, dryers, oven, film desiccation and food processing. For domestic application, humidity control is required for living environment in buildings, cooking control for microwave oven etc. Figure 3.1 shows the humidity sensor the widely being used in industry.